Inter- and transdisciplinary scenario construction to explore future land-use options in southern Amazonia - Regine Schönenberg; Rüdiger Schaldach; Tobia Lakes; Jan Göpel; Florian Gollnow (Ecology and Society, 2017)
Our aim with this paper is to present a novel approach for developing story lines and scenarios by combining qualitative knowledge and quantitative data from different disciplines and discussing the results with relevant decision makers. This research strategy offers a solid foundation for perspectives into the future. The "laboratory" is the Brazilian Amazon, one of the hotspots of land-use change where local and global interests both collide and converge: local livelihoods are affected by regional and global climate change and by the loss of biodiversity caused by local and global economic interests in agro-industrial land use; such use contributes, in turn, to climate change. After decades of diverse policy interventions the question arises: What can we learn from past trajectories for a more sustainable development in the future? To answer this question, we combined qualitative story lines for the region, reviewed by local experts, with quantitative land-use scenarios, to study their regional and local manifestations in space. These results were then discussed again with local and national experts. Our findings suggest that in-depth knowledge of the diverging perspectives at a very local level is a fundamental prerequisite for downscaling global scenarios and upscaling local approaches to sustainable land-use management and thus, to producing communicable and applicable results.